ARABIC TEACHERS’ COMPETENCE: A CASE OF MADRASAH SCHOOLS IN MALUKU - Saidah, Ummu; Bin-Tahir, Saidna Zulfiqar; Mufidah, Nuril (Ijaz Arabi Journal of Arabic Learning, 2018)
In reality, not a few teachers who have been certified as educators are less competent in teaching the field of study. Many teachers are also able to master the subject matter, but they have difficult to present the material. This research applied a qualitative method using a case study design. It was carried out in the State Madrasah schools of Salahutu District, Central Maluku Regency. This research was conducted from August to 02 November 2017. The subjects of this study were 3 Arabic teachers, two principals and 6 class students totaling 12 informants. Based on the results, it was found that the pedagogic competence of Arabic language teachers was still relatively low due to the several indicators that were not implemented during the learning process. The personality’s competence of Arabic language teachers is relatively good compared to their pedagogical competence. The lacks of training, facilities, and rewards have caused the low educational competence of teachers. Their personal competence is due to strict supervision and their commitment to building the ummah as followers of religion and not because of their profession as teachers. Students are motivated to learn Arabic due to the motivation is given by the teacher, the mu'amalah is good between teachers and students, and there is a continuous and rigorous evaluation.